Investigation Of Port Maintenance And Infrastructure Workers At Chennai Port Trust - S, Sajith.; Elumalai, D. (Journal of Neonatal Surgery, 2025)
This study examines the characteristics and challenges faced by port trust goods and carrier workers at Chennai Port. Demographic analysis indicates a predominantly male workforce with a variety of job roles and levels of experience. While customer satisfaction is generally high, indicating effective operations, the study identifies areas for improvement. Recommendations include enhancing training programs, improving communication, adopting new technologies, and increasing stakeholder engagement. These measures aim to inform policy and practice, thereby improving the well-being of port trust workers and boosting the overall efficiency of port operations